The uterine rupture and bladder rupture on a pregnant mother with previous cesarean section after partum management on midwife - Dewi Karlina Rusly; Hilwah Nora; Kartini Hasballah (Syiah Kuala University, 2013)
A-case report about the process and impact of the vaginal birth after section caesarean in rural on a pregnant woman who has previous cesarean. This is the case of Mrs H, 30 years old in aterm gestational age with singleton intra partum fetal death, previous cesarean section, with suspected uterine rupture. She wasadmitted to RSUZA hospital due to unprogress labour, sent from midwife after failed of labour. In the hospital the catether was inserted and we found hematuria. She had been control for pregnancy in the hospital ofmother and baby for two times and the last 2 weeks was said the baby still in good condition. She was had the previous cesarean 5 years ago on second pregnancy due to unprogress labour and the incision was transversal,and also had the extraction vaccum history for delivered the first pregnancy. She already get information to delivered this third baby in the hospital, but she was coming to midwife due to contraction, and the orificium uretra extrenum was opened 8 cm, so the midwife try to delivered the baby for 1 hour, and because failed, the midwife sent to the hospital. After 3 hours, she was administered to the hospital the opened of orificium uteri was 10 cm and we found hematuria. During the way she was transferring to hospital she feels the movement of the baby was lost. When she administered in hospital the blood pressure was 100/70 mmHg, with the heart rate 100 times/ minute. She was complaints pain in the previous cesarean scar 3 hours later, and lost of fetalmovement since 1 hours ago. On ultrasound examination there was intrapartum fetal death. We decided to do laparotomy exploration due to suspected uterine rupture. On the operation we found 200 cc blood clot inside the layer of peritoneum, and after the peritoneum was cleaned and opened we could see the upper of the fetal head out side the uterus which intrapartum fetal death, with the large uterine rupture along the previous cesarean incision about 12 cm length. We also found the ballon of folley catheter outside the bladder, so weconfirm to urology and also found there was a bladder rupture grade IV with 14 cm lengths on the posterior bladder. After delivered the baby, The uronologist did repair bladder rupture and the bladder was inserted the spolling folley catheter with NaCl 0.9% from the upper bladder for maintenance the drainage of the bladder so it keep clean during in the ward and the folley cateter also inserted from the uretra. The procedure was continued with the obstetrician to do repairation of the uterine rupture. In the ward she was hospitalized for 14 days to maintain the bladder. From this case, we would like to assess the patophysiology of uterine rupture and bladder rupture which cause the mortality and morbidity of mother and baby. The uterine rupture has correlation withlate and false of management of delivery which result in intra partum fetal death and bladder rupture that was explained in this paper.